Evidence of secondary neuronal intestinal dysplasia in a rat model of chronic intestinal obstruction - Gálvez, Y; Skába, R; Vajtrová, R; Frantlová, A; Herget, J (Journal of investigative surgery, 2004)
The etiology of neuronal intestinal dysplasia remains largely unknown. There is, however, supporting evidence of the existence of Hirschprung's disease or chronic intestinal obstruction associated with neuronal intestinal dysplasia. With the aim of investigating the possible development of neuronal intestinal dysplasia linked to chronic intestinal obstruction, we have examined the enteric nervous system response to long-term obstruction in a rat model. Three different surgical techniques were tested in Wistar male rats. In animals that survived longer than the cutoff chronic intestinal obstruction point (6 weeks), full-thickness biopsies and acetylcholinesterase (AChE), NADH, hematoxylin-eosin, and anti-S100 protein stainings were performed. The results of our model indicate that chronic intestinal obstruction induced different degrees of enteric nervous system dysplasia, including histological features of neuronal intestinal dysplasia. The relationship between chronic intestinal obstruction and anomalies of the enteric nervous system, including neuronal intestinal dysplasia, needs to be further studied.
Keywords: Animals; Acetylcholinesterase; Hirschsprungova nemoc; Rats; Rats, Wistar; biopsie; Intestinal Obstruction; neurony; Hirschsprung Disease; Neurons; střevní nervový systém; Male; modely nemocí na zvířatech; acetylcholinesterasa; Biopsy; střevní obstrukce; Disease Models, Animal; krysa rodu Rattus; chronická nemoc; zvířata; mužské pohlaví; Chronic Disease; Enteric Nervous System; potkani Wistar